Japanese Pop Culture for Language Learning: A Quantitative Study on Motivation and Japanese Language Skills Among Japanese Language Students in Indonesia - Dewanty, Via Luviana; Farisya, Ghaida; Kusrini, Dewi (KIRYOKU, 2025)
This quantitative study investigates the impact of Japanese Pop Culture (JPC) on the motivation and Japanese language skills of Japanese language study program students in Indonesia. This research is based on theories about the role of pop culture in foreign language learning, especially the role of JPC in students' interest in Japanese. Questionnaires related to interest in learning Japanese, motivation to learn Japanese, activities associated with JPC outside of lectures, and improving Japanese language skills were distributed to 70 Japanese language study program students from several universities in Indonesia. The results of data analysis show that JPC plays a big role in motivating students to study Japanese and improve their Japanese language skills. Based on the questionnaire results, all respondents were interested in and liked JPC. Over half of the respondents were JPC fans before becoming Japanese language study program students. Regarding motivation to study Japanese, as many as 63% of students were motivated to become students in the Japanese language study program because they liked JPC before. More than 80% of respondents carry out JPC activities by watching anime and listening to Japanese music. Half of the respondents stated that they could get to know Japan and understand Japanese people better by consuming JPC. In contrast, more than 80% of respondents felt benefits in increasing their ability and understanding of Japanese after consuming JPC. It is hoped that the results of this research can be used as a basis or reference for further research on using JPC in Japanese language learning.